From Basel I to Basel III: a cost-benefit analysis of the international regulatory framework for banks - Bruccini, Emanuele (2018)
The aim of this paper is to analyze the macroeconomics consequences of Basel III, which will be completely implemented in 2019. Starting with an analysis of the guidelines of Basel I and Basel II and briefly discussing about the recent Financial Crisis, I focus my attention on Basel III, trying to analyze its impacts. If the new Regulatory would impact the stability of the financial and bank system, at the same time it can have some negative impacts on the real economy, especially in regards to the operability of the banks.